A descriptive study of nature sound In open-plan office on cognitive performance of employees - Ahmad Dahari, Munirah; Mohd Mahudin, Nor Diana (Asian Scholars Network, 2019)
Despite being the preferred office setting especially for organizations with a huge number of employees, the open-plan office brings together with it a number of drawbacks. Acoustical distraction as one of the unresolved issues in open-plan office settings requires further intervention to minimize its negative effect, especially to the employees' performance. The study intended to mask the existing noise in the office by including nature sounds in such settings to see the impact on employees' cognitive performance. A quasi-experiment was conducted to fifty (50) administrative employees (female, n = 35, male, n = 15) in which they were exposed to four types of sound (i.e.: biophony nature sound, machine-generated noise, geophony nature sound, and human-generated noise) accordingly in their office for one week for each sound, followed by an error detection task at the end of every week. The descriptive analysis indicated that biophony sound has a positive impact on employees' cognitive performance (M = 9.48, SD = 0.65), while human-generated noise decreases such performance significantly with (M = 5.66, SD = 2.47). The study contributed to vast implications and recommendations for future research. To conclude, nature sounds subsidized to one's cognitive performance while noise coming from humans reduced such performance.